Eye Gaze Assistance for a Game-Like Interactive Task. (11th June 2008) - Gedeon, Tamás (Tom) D.; Zhu, Dingyun; Mendis, B. Sumudu U.
Abstract : Human beings communicate in abbreviated ways dependent on prior interactions and shared knowledge. Furthermore, humans share information about intentions and future actions using eye gaze. Among primates, humans are unique in the whiteness of the sclera and amount of sclera shown, essential for communication via interpretation of eye gaze. This paper extends our previous work in a game-like interactive task by the use of computerised recognition of eye gaze and fuzzy signature-based interpretation of possible intentions. This extends our notion of robot instinctive behaviour to intentional behaviour. We show a good improvement of speed of response in a simple use of eye gaze information. We also show a significant and more sophisticated use of the eye gaze information, which eliminates the need for control actions on the user's part. We also make a suggestion as to returning visibility of control to the user in these cases.